PENGARUH METODE PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Pajriana, Ica; Pujilestari, Pujilestari (Media Pendidikan Matematika, 2016)
The aim of this study was to determine the effect of the use of learning methods Team Assisted Individualization (TAI) on learning outcomes of students' mathematics class VII MTs NW Montong Baan academic year 2014/2015. This type of research is experimental research, form design used was nonequivalent control group design. Sampling was done by purposive sampling technique. The sample in this study amounted to 39 students for the experimental class, and 38 students in the control class. Data in this study were drawn by providing initial test and final test to students in grade samples. Data collection techniques using objective tests that have been tested for validity and reliability by the validator. Data were analyzed using t-test. From the result of the calculation, shows that student learning outcomes group teaching methods Team Assisted Individualization (TAI) was higher than the control group, the t test results are known thitung 2,392 and ttabel 1,995 at significant level of 5% by dk = 75 because thitung > t table (2,392> 1,995), the Ha accepted and H0 is rejected, which means learning methods Team Assisted Individualization (TAI) effect on learning outcomes mathematics class VII MTs NW Montong Baan school year 2014/2015.